Индия: фокус на Африку? (India: Focus Africa?) - Sharapova Aleksandra V. (St. Petersburg University Press, 2022)
The article touches upon India’s policy towards Africa. Since the Roman era Africa has always caught the attention of developed countries, as the continent was an enormous field for exploring, a complete terra incognita. Later a new wave of interest came as Africa possessed abundant resources and had connections to commercial maritime routes: the Red Sea, the Persian Gulf, the Indian Ocean, the Atlantic Ocean. Today India does its best not only to become a trusted trade and political partner for African states, but also to win their sympathies. For example, Indian leaders never tire of reminding that India — just like Africa — fought against colonialism, thereby opposing itself to the former colonial empires and emphasizing its common historical and cultural background with Africa. The author reviews Indian foreign policy, diaspora influence, and Indian military presence on the continent. Meanwhile some countries, for example the U.S. or Japan, remain wary of Chinese wide-spreading influence, especially in Africa, where a new Chinese military base was recently built. In that regard new alliances are forming, the balance of power is shifting. A comparative analysis of Indian, Chinese, and U.S. policy towards Africa was carried out, considering the prospects of international relations between Africa and its key partners.